Anti-angiogenic effect of high-dose resveratrol in a swine model of metabolic syndrome - Robich, Michael P. (2010)
BACKGROUND: Resveratrol has been reported to induce angiogenesis in ischemic tissue. We hypothesized that high-dose resveratrol would improve native angiogenesis in a swine model of metabolic syndrome and chronic myocardial ischemia. METHODS: Yorkshire swine were fed a normal diet (Control, n=7), hypercholesterolemic diet (HCD, n=7), or hypercholesterolemic diet with supplemental resveratrol (100 mg/kg/day orally, HCD-R, n=7) beginning one month prior to surgery. Chronic ischemia was created by placing an ameroid constrictor on the left circumflex coronary artery. After 7 weeks, swine underwent functional MRI, coronary angiography, and serum and heart tissue harvest for analysis. RESULTS: HCD-R animals had lower body mass index (p<0.001), total cholesterol (p<0.001), LDL (p<0.001), blood glucose levels (p<0.001), and systolic blood pressure (p=0.03) than HCD animals. There was no difference in regional myocardial function at 7 weeks (p=0.25). Coronary angiograms revealed no difference in Rentrop collateral scores (p=0.68). Staining for PECAM-1 demonstrated higher capillary density in the Control group (vs. HCD and HCD-R, p=0.02). Immunoblotting demonstrated decreased expression of the pro-angiogenic protein vascular endothelial (VE)-cadherin (p=0.002) and an increase in anti-angiogenic proteins angiostatin (p=0.001) and thrombospondin (p=0.02) in the HCD and HCD-R groups. Matrix metalloprotease 2 (MMP2)(p=0.47) and MMP9 (p=0.12) were not different among groups. CONCLUSION: Supplemental resveratrol positively modified cardiovascular risk factors including body mass index, cholesterol, glucose tolerance, and systolic blood pressure. However it did not increase native collateral formation in the ischemic myocardium. This may be a result of increased angiostatin and thrombospondin leading to decreased expression of VE-cadherin and other pro-angiogenic factors.